Copolymerization of Carbon–carbon Double-bond Monomer (Styrene) with Cyclic Monomer (Tetrahydrofuran) - Fouad Sari; M. I. Ferrahi; M. Belbachir (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2012)
We reported in this work that the cationic copolymerization in one step takes place between carbon–carbon double-bond monomer styrene with cyclic monomer tetrahydrofuran. The comonomers studied belong to different families: vinylic and cyclic ether. The reaction is initiated with maghnite-H+ an acid exchanged montmorillonite as acid solid ecocatalyst. Maghnite-H+ is already used as catalyst for polymerization of many vinylic and heterocyclic monomers. The oxonium ion of tetrahydrofuran and carbonium ion of styrene propagated the reaction of copolymerization. The acetic anhydride is essential for the maintenance of the ring opening of tetrahydrofuran and the entry in copolymerization. The temperature was kept constant at 40°C in oil bath heating for 6 hours. A typical reaction product was analyzed by 1H-NMR, 13C-NMR and IR and the formation of the copolymer was confirmed. The reaction was proved by matched with analysis. The maghnite-H+ allowed us to obtain extremely pure copolymer in good yield by following a simples operational conditions. © 2012 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)